2009
DOI: 10.3354/meps08148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sinking spring phytoplankton blooms on lipid content and composition in suprabenthic and benthic invertebrates in a cold ocean coastal environment

Abstract: Lipids were measured in 19 suprabenthic and benthic invertebrate taxa from 5 phyla to determine their responses to a sinking spring diatom bloom. In Conception Bay, as in many areas of coastal Newfoundland, Canada, benthic organisms experience sub-zero temperatures year round. Among specimens collected at depths between 210 and 220 m, the small mysid Erythrops erythrophtalma had, on average, the highest lipid concentration (6% of wet weight), while a holothurian (Order Apodida) had the lowest (0.3%). In E. ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 64 publications
2
22
0
1
Order By: Relevance
“…These microalgae also contribute to benthic food webs, and in some cases the presence of their characteristic FAs in benthic organisms indicates a trophic connection between pelagic and benthic food webs (Kharlamenko et al 1995, Graeve et al 1997, Parrish et al 2009). Benthic food webs also rely on macroalgae, vascular plants (such as mangroves and seagrass), and bacteria, and these food sources also have characteristic FA compositions that can be used to identify their contributions to higher trophic levels (Dalsgaard et al 2003).…”
Section: Primary Producer and Bacterial Famentioning
confidence: 99%
“…These microalgae also contribute to benthic food webs, and in some cases the presence of their characteristic FAs in benthic organisms indicates a trophic connection between pelagic and benthic food webs (Kharlamenko et al 1995, Graeve et al 1997, Parrish et al 2009). Benthic food webs also rely on macroalgae, vascular plants (such as mangroves and seagrass), and bacteria, and these food sources also have characteristic FA compositions that can be used to identify their contributions to higher trophic levels (Dalsgaard et al 2003).…”
Section: Primary Producer and Bacterial Famentioning
confidence: 99%
“…The rationale behind the use of these 9/ 7 ratios is elongation of the diatom 16:1 7 to 18:1 7, but they could be biased if there was a significant intake of bacterial 18:1 7. Low and seasonally highly variable ratios have been observed in echinoderm gonads [102,103].…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…This multivariate technique handles a large amount of variables simultaneously, and has been used by organic geochemists to determine organic matter sources and degradation of suspended and sinking particles in the oceans [110,111]. We have used PCA to determine marine, terrestrial, and anthropogenic organic inputs, and trophic relationships (e.g., [100,102,104,[112][113][114]). Fatty acid PCA continues to have a strong following [115][116][117], but more sophisticated multivariate statistical analyses are emerging too (see below).…”
Section: Multivariate Data Analysismentioning
confidence: 99%
“…In terms of MUFA, the polychaete was characterized by relatively elevated levels of 17:1 (1 isomer; 7.1 %), 20:1 (4 isomers; 10.3 %) and 22:1ω7 (6.6 %). This fatty acid composition is intermediate between that of polychaetes at deep hydrothermal vents (Phleger et al 2005) and those found in cold coastal benthos (Parrish et al 2009). …”
Section: Lipid Composition Of Fish Tissues and Gut Contentsmentioning
confidence: 63%
“…The crustacean was rich in PUFA (40 % of total fatty acids), principally 20:5ω3 (10.1 %) and 22:6ω3 (18.5 %), and was characterized by moderate 16:1ω7 (6.8 %), 18:1ω7 (6.4 %) and 18:1ω9 (9.1 %) levels. This combination of fatty acids, in particular 18:1ω9, 20:5ω3 and 22:6ω3 together, is typical of crustaceans (Parrish et al 2009). Although the polychaete was less rich in ΣPUFA (30.2 %), and contained very little 22:6ω3 (0.5 %), a large relative amount of 20:5ω3 (16.5 %) was present.…”
Section: Lipid Composition Of Fish Tissues and Gut Contentsmentioning
confidence: 86%